2020
DOI: 10.1007/s10899-020-09951-4
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the prevalence of gambling harm among active duty military personnel: a systematic scoping review

Abstract: The prevalence of gambling harm among active duty military personnel is a largely unexplored topic. With different forms of social gambling often found within (or in close proximity to) military bases around the world, understanding the extent of gambling activities and consequent harms occurring within military contexts warrants further attention. This review aims to identify, describe and thematically synthesise published literature on gambling harm and related issues among active duty military personnel. Sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Several studies internationally have reported that rates of problem gambling in veterans range from 2% to 29% and exceed rates reported for non-veterans. Gambling problems are also reported as frequently co-occurring with mental ill health disorders; a recent study reported that 41% of veterans being treated for gambling concerns have also experienced mood disorders at some point in their lifetime (Ahern et al, 2015, Etuk et al, 2020Freeman et al, 2019;Levy & Tracy, 2018;Paterson et al, 2020;Shirk et al, 2018;van der Mass & Nower, 2020).…”
Section: Behaviours Across Studiesmentioning
confidence: 99%
“…Several studies internationally have reported that rates of problem gambling in veterans range from 2% to 29% and exceed rates reported for non-veterans. Gambling problems are also reported as frequently co-occurring with mental ill health disorders; a recent study reported that 41% of veterans being treated for gambling concerns have also experienced mood disorders at some point in their lifetime (Ahern et al, 2015, Etuk et al, 2020Freeman et al, 2019;Levy & Tracy, 2018;Paterson et al, 2020;Shirk et al, 2018;van der Mass & Nower, 2020).…”
Section: Behaviours Across Studiesmentioning
confidence: 99%
“…The most commonly cited reasons for non-help seeking include perceived stigma and the practical accessibility of support (Hom et al, 2017 ; Kantor et al, 2017 ; Possemato et al, 2018 ). The increased availability of opportunities to gamble nowadays, the stigma associated with disordered gambling, and the tendency for veterans to use gambling to cope with the consequences of trauma may combine and prompt lower levels of help-seeking (Paterson et al, 2021 ). Mental health difficulties related to PTSD and GD may thus go undetected among veterans.…”
Section: Introductionmentioning
confidence: 99%